Thermal collapse of spin polarization in half-metallic ferromagnets - Lezaic, M.; Mavropoulos, Ph.; Enkovaara, J.; Bihlmayer, G.; S. Blügel (PHYSICAL REVIEW LETTERS, 2006)
We propose two novel approaches to study the temperature dependence of the magnetization and the spin polarization at the Fermi level in magnetic compounds, and apply them to half-metallic ferromagnets. We reveal a new mechanism, where the hybridization of states forming the half-metallic gap depends on thermal spin fluctuations and the polarization can drop abruptly at temperatures much lower than the Curie point. We verify this for NiMnSb by ab initio calculations. The thermal properties are studied by mapping ab initio results to an extended Heisenberg model which includes longitudinal fluctuations and is solved by a Monte Carlo method.